Aplicação do BIM no setor de infraestrutura: estudo em uma companhia de água e esgoto do RN - Souza, Maria Cecilia de Souza e (2020)
Infrastructure is considered a fundamental factor for the productivity and economic development of a country, given that it integrates markets, connects economic agents and helps with cost reduction and information flow. In many countries, infrastructure investment is viewed as a political and economic priority. Brazil, however, is one of the countries that invests the least in the sector: currently less than 2% of its Gross Domestic Product (GDP), while China, for example, invests 7% of its GDP. In addition to being scarce and poorly applied, part of the Brazilian investment in infrastructure ends up retained in suspended construction projects which, in 2017, represented 18,5% of the halted projects, according to the Brazilian Ministry of Planning. Having in mind the relevance and benefits of BIM (Building Information Modeling) for the construction industry, the Brazilian Federal Government has started to require an adjustment of federal public administration agencies - among them the Ministry of Infrastructure - to BIM, through the Decrees 9.983/2019 and 10.306/2020. In view of these circumstances, there is a growing interest and importance in analyzing and evaluating the applicability of BIM in infrastructure enterprises. The general objective of this dissertation is to propose guidelines to facilitate the introduction of BIM in processes of the projects sector of a public sanitation company in the state of Rio Grande do Norte, Brazil. For this purpose, the applied research method was the Design Science Research, which divides the conduction of activities in five main steps (awareness of the problem, suggestion, development, evaluation and conclusion), involving an empirical study in the projects sector of a public sanitation company (the Water and Sewage Company of Rio Grande do Norte - Caern), a diagnostic study about BIM adoption in public agencies in Rio Grande do Norte (18 agencies, in total), the proposal of a method (artefact) with guidelines for the adoption of BIM in projects of water supply and sewerage networks and its evaluation in regards to generality, operationality and ease of use by applying a focus group technique. Results revealed that the projects sector at Caern still operates in a traditional manner, and deals constantly with a lack of graphical standards and procedures, scarcity of technological solutions and with non-collaborative work; that half of the agencies analyzed in the diagnostic study have developed initiatives for BIM adoption; that the proposed method was well evaluated, considered easy to use, functional and generalizable, albeit hard to implement. Generally, the infrastructure sector noticeably still lacks studies and delimitations for the use of BIM, and this research contributes to BIM insertion in its workflow and processes.